2013
DOI: 10.1371/journal.pone.0074425
|View full text |Cite
|
Sign up to set email alerts
|

Development of Novel Rifampicin-Derived P-Glycoprotein Activators/Inducers. Synthesis, In Silico Analysis and Application in the RBE4 Cell Model, Using Paraquat as Substrate

Abstract: P-glycoprotein (P-gp) is a 170 kDa transmembrane protein involved in the outward transport of many structurally unrelated substrates. P-gp activation/induction may function as an antidotal pathway to prevent the cytotoxicity of these substrates. In the present study we aimed at testing rifampicin (Rif) and three newly synthesized Rif derivatives (a mono-methoxylated derivative, MeORif, a peracetylated derivative, PerAcRif, and a reduced derivative, RedRif) to establish their ability to modulate P-gp expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 55 publications
1
25
0
Order By: Relevance
“…Finally, similar conclusions on the location of the DBS and residues involved in drug binding were reported recently . In contrast, a recent study toward P‐gp activation with rifampicine‐derived molecules identified two molecules that may induce P‐gp expression against paraquat‐induced cytotoxicity, thus constituting a new approach for the treatment of toxicologic phenomena.…”
Section: Structure‐based Drug Discovery In Mdrsupporting
confidence: 78%
“…Finally, similar conclusions on the location of the DBS and residues involved in drug binding were reported recently . In contrast, a recent study toward P‐gp activation with rifampicine‐derived molecules identified two molecules that may induce P‐gp expression against paraquat‐induced cytotoxicity, thus constituting a new approach for the treatment of toxicologic phenomena.…”
Section: Structure‐based Drug Discovery In Mdrsupporting
confidence: 78%
“…Although the mechanism of action of P-gp inducers remains unclear, it is known that P-gp induction is regulated by nuclear factors, such as pregnane X receptor (PXR), constitutive androstane receptor (CAR), nuclear factor erythroid-derived 2-related factor (Nrf2), Y-box binding protein-1 (YB-1), nuclear factor Y (NF-Y), nuclear factor-κB (NF-κB), liver X receptor (LXR), farnesoid X receptor (FXR) and peroxisome proliferator-activated receptors α and γ (PPARα and PPARγ) [ 3 , 51 , 55 , 56 , 57 ]. The mechanism of action of P-gp activators suggests the involvement of the NBDs: (a) speed-up of the transport velocity, resulting in an increased conversion of ATP or (b) enhanced ATP affinity for the NBDs, leading to increased binding [ 58 ]; or conformational changes in the TMDs due to the binding of the compound in a specific ligand-binding site, which stimulates the substrate efflux on another ligand-binding site [ 20 ].…”
Section: Overview Of the Abc Transportersmentioning
confidence: 99%
“…In humans, ABC transporters comprise 49 proteins distributed by seven subfamilies (ABCA–G) with about 20 carriers involved in xenobiotics transport [ 3 , 14 ]. Several in vitro and in vivo studies have shown that the expression and activity levels of efflux transporters are modulated by the presence of inhibitors, inducers and/or activators [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, it is known that P‐gp is present in both tumor and normal cells, exporting xenobiotics in the intestine, liver, kidney, pancreatic and bile ducts, renal proximal tubule, placenta, testis and blood–brain barrier, as well as in lymphocytes (Choudhuri & Klaassen, ; Vilas‐Boas et al ., ). P‐gp is inducible by many drugs, including dexamethasone, rifampicin, hypericin and hyperforin (St John's wort antidepressants), and chemotherapeutic agents such as doxorubicin, daunorubicin and vimblastine (Chaudhary & Roninson, ; Dinis‐Oliveira et al ., ; Hu et al ., ; Tian et al ., ; Vilas‐Boas et al ., ; Zhou, ). Considering all of the mechanisms in which P‐gp is involved, it can be concluded that P‐gp plays a very important role in defending cells against its toxic substrates, avoiding their intracellular accumulation.…”
Section: Introductionmentioning
confidence: 97%
“…Considering all of the mechanisms in which P‐gp is involved, it can be concluded that P‐gp plays a very important role in defending cells against its toxic substrates, avoiding their intracellular accumulation. Accordingly, strategies to increase P‐gp expression and/or activity may be viewed as potential antidotal pathways to prevent P‐gp substrate‐mediated toxicity and, therefore, an alternative therapeutic strategy to implement in the near future, in intoxication scenarios (Dinis‐Oliveira et al ., ; Silva et al ., ; Vilas‐Boas et al ., ).…”
Section: Introductionmentioning
confidence: 97%